Review on Vision Based Real Time Fingertip Detection Approaches - Jacob, Ritty; N, Sugitha (Iraqi Journal of Science, 2023)
Computer vision is an emerging area with a huge number of applications. Identification of the fingertip is one of the major parts of those areas. Augmented reality and virtual reality are the most recent technological advancements that use fingertip identification. The interaction between computers and humans can be performed easily by this technique. Virtual reality, robotics, smart gaming are the main application domains of these fingertip detection techniques. Gesture recognition is one of the most fascinating fields of fingertip detection. Gestures are the easiest and productive methods of communication with regard to collaboration with the computer. This analysis examines the different studies done in the field of fingertip identification. A survey is also included using various methods and measures. A few difficulties and examination bearings are additionally featured. Various researchers utilize fingertip recognition in HCI frameworks with numerous applications like identifying persons, intelligent homes, and so forth. A correlation chart of various experts is an additional result mentioned in this paper.